KESALAHAN UMUM DALAM PENULISAN ARTIKEL ILMIAH MAHASISWA PERGURUAN TINGGI - Septian Eko Rahmanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article to describe the forms of errors in writing scientific articles and their corrections as an effort to develop strategies in writing scientific papers. Through a qualitative approach, the results of this research will be explained in an interactive descriptive manner. The data used is in the form of errors in writing scientific articles through several scientific disciplines obtained through literature including, writing letters, writing words, using punctuation marks, and grammar in articles. The data source uses a literature review of scientific articles written by students from various higher education institutions. Data collection through literature study. Data analysis through content analysis in scientific articles using listening, reading and note-taking techniques. Data validity uses theoretical triangulation and observer persistence. The research results show that there are common errors in writing scientific articles in the form of errors in the form of writing capital letters, small letters and italics; word writing errors; punctuation errors; grammatical errors, and citation errors as reference sources. These error form criteria will be used as material for developing the quality of learning to write scientific articles among students at universities. This is a form of developing implementation and strategies in writing scientific papers.